Phenosafranin-Based Colorimetric-Sensing Platform for Nitrite Detection Enabled by Griess Assay - Hou, Jingzhou (Sensors (Basel), 2020)
A facile and effective colorimetric-sensing platform based on the diazotization of phenosafranin for the detection of [Formula: see text] under acidic conditions using the Griess assay is presented. Diazotization of commercial phenosafranin produces a color change from purplish to blue, which enables colorimetric quantitative detection of [Formula: see text]. Optimal detection conditions were obtained at a phenosafranin concentration of 0.25 mM, HCl concentration of 0.4 M, and reaction time of 20 min. Under the optimized detection conditions, an excellent linearity range from 0 to 20 μM was obtained with a detection limit of 0.22 μM. Favorable reproducibility and selectivity of the colorimetric sensing platform toward [Formula: see text] were also verified. In addition, testing spiked ham sausage, bacon, and sprouts samples demonstrated its excellent practicability. The presented colorimetric sensing platform is a promising candidate for the detection of [Formula: see text] in real applications.